Friction and wear properties of plasma-sprayed Cr2O3–BaCrO4 coating at elevated temperatures. Issue 6 (15th March 2022) - Su, Weiming; Niu, Shaopeng; Huang, Yicong; Wang, Chao; Wen, Yuyin; Li, Xin; Deng, Chunming; Deng, Changguang; Liu, Min
Abstract: Chromium oxide is widely used as a tribological coating material in high-temperature applications requiring high wear resistance and lubricity. Herein, an attempt has been made to further improve the friction and wear properties of Chromium oxide coatings by incorporating BaCrO4 as a high temperature solid lubricant. The Cr2 O3 -10 wt% BaCrO4 high temperature self-lubricating ceramic was prepared by atmospheric plasma spraying (APS). The friction and wear characteristics of the Cr2 O3 –BaCrO4 composite coating coupled with Si3 N4 balls from 25 °C to 700 °C were measured by a high temperature tribological tester and compared with that of pure Cr2 O3 coating. Results showed that the Cr2 O3 –BaCrO4 coating possessed compact and lamellar structure with features of chromates fully spreading in it. Cr2 O3 –BaCrO4 coating did not exhibit improved tribological performance until the temperature was elevated to 400 °C and above. Surface brittle fracture could be mainly responsible for the poor tribological properties of Cr2 O3 –BaCrO4 coating at 25 °C and 300 °C. The adaptive formation of BaCrO4 at 400 °C and above on the worn surfaces of Cr2 O3 –BaCrO4 coating played a vital role in improving the frictional force on ceramic surfaces and the wear resistance of the coatings and counterpart balls despite the significant decomposition of BaCrO4 during spraying.